Organizational life cycle sustainability assessment (OLCSA) for a higher education institution as an organization: a systematic review and bibliometric analysis - Wafa, Wafaurahman; Sharaai, Amir Hamzah; Matthew, Nitanan Koshy; Abdullah J Ho, Sabrina; Akhundzada, Noor Ahmad (MDPI AG, 2022)
Life cycle sustainability assessment (LCSA) is an approach utilized for products to analyze their sustainability indicators. However, no definite study has determined the sustainability of an organization using the LCA approach. This review focuses on a systematic review and bibliometric analysis of the OLCSA in University. The literature was searched in the Scopus online database considering PRISMA guidelines, and VOSviewer software was used for three types of bibliometric analysis, i.e., co-authorship, co-occurrence, and co-citation were analyzed with their units of analysis. The results show that there is no specific study that has found or assessed the LCSA of an organization. However, 17 articles on O-LCA and 2 on SO-LCA were found, and there were numerous articles available about ELCC in the literature. Researchers mostly used UNEP guidelines for O-LCA, in line with ISO standards. However, they used NPV for E-LCC. Based on VOSviewer software, Matthias Finkbeiner, Forin, Martínez-Blanco Julia, Berger Markus, Lehman, Loss, Manzardo, Scipion, Hall, and Weldu are co-authors. The keyword of “life cycle” was broadly used, and the most cited source was the “International Journal of Life Cycle Assessment”. Adoption of the LCSA framework is recommended for O-LCSA studies to estimate organizations’ sustainability, and to ensure quality education contributing the fourth SDGs.